2005
DOI: 10.1128/jb.187.18.6333-6340.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response ofEscherichia colito External Zinc

Abstract: Transcriptional response of Escherichia coli to extracellular zinc was studied using DNA microarray and S1 mapping assays. Addition of external zinc induced the expression of zinc exporter ZntA and inhibited the expression of zinc importer ZnuC. In the continuous presence of zinc, ZnuC repression took place at lower zinc concentrations than ZntA induction. The microarray assay indicated that the addition of excess external zinc induces the expression of many genes that are organized in the regulon for cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 33 publications
9
82
0
Order By: Relevance
“…But, the level of htrA mRNA was significantly increased by copper in the cpxAR null mutant because htrAp is induced by sigma-E activation, as seen previously for zinc shock. 22) Transcripts from 11 promoters, cpxPp, ftnBp, htrAp, ppiAp, ybaJp1, yccAp, ydeHp, yihEp, yebEp, yobBp, and yqjAp, were detected without copper in the wild type, whereas two promoters, spyp and ycfSp, were silent in the absence of copper (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But, the level of htrA mRNA was significantly increased by copper in the cpxAR null mutant because htrAp is induced by sigma-E activation, as seen previously for zinc shock. 22) Transcripts from 11 promoters, cpxPp, ftnBp, htrAp, ppiAp, ybaJp1, yccAp, ydeHp, yihEp, yebEp, yobBp, and yqjAp, were detected without copper in the wild type, whereas two promoters, spyp and ycfSp, were silent in the absence of copper (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 promoters, 10 promoters, cpxPp, ftnBp, spyp ybaJp1, yccAp, ycfSp, ydeHp, yebEp, yobBp, and yqjAp, were newly determined by this experiment, while three promoters, htrAp, ppiAp, and yihEp, have been reported by others. [22][23][24] The À10 and À35 elements of all 13 promoters were found as typical sequences for recognition by sigma-D (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of Zn(II) used was chosen based on the toxicity experiments, which revealed that 400 μM Zn(II) results in slower growth (as opposed to a lethal concentration leading to no growth). Furthermore, several previous investigations assessing the genome-wide transcriptional response of E. coli to zinc demonstrated that [Zn(II)] >100 μM is sufficient to observe a change in the transcript levels of the above-mentioned transporters, albeit under different media compositions (46,47). While the addition of Zn(II) led to an increase in zntA transcription and a decrease in znuA transcription, as expected, we observed no significant difference between wild type and ΔslyD strains grown in the presence or absence of oxygen (Figures S13 and S15).…”
Section: Impact Of the Slyd Deletion On Transcriptional Metalloregulamentioning
confidence: 99%
“…71) In the presence of excess Zn 2+ , ZntR activates transcription of zntA for export of excess zinc. 63,72) The ZntR-binding site consists of the inverted repeat of ACT-CTGGAGTC.…”
Section: Zntr Transcription Factormentioning
confidence: 99%
“…63,67,72) The Zur-binding site consists of the inverted repeat of GAAATGTTATA with the spacer of mono-nucleotide. 63,67,72) 4.6.3. ZraS-ZraR two-component system.…”
Section: Zur Transcription Factormentioning
confidence: 99%